Direito à internet no Brasil: a necessidade de elevação à categoria de direito fundamental - Adler, Raniel Rotta (2024)
This article analyzes the internet as a right, focusing on the need for such a right be elevated to the category of fundamental right, so that the legal system provides effectiveness in guaranteeing given to the population. To this end, the work discussed the emergence of new fundamental rights, the guarantee of a dignified existence for human beings depending on access to the internet and on the digital transformation of State. The research also analyzed current legislation regarding the guarantee of internet access to the entire population and data relating to connectivity in Brazil, which justify the need for the right to internet is classified as a fundamental right. It was argued that the elevation of this right to a fundamental right must occur through a Proposed Amendment to the Constitution (PEC), also analyzing two PECs in progress in the National Congress, presented with this objective.